2015
DOI: 10.3906/tar-1404-41
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different priming applications on seed germination and some agromorphological characteristics of bread wheat (Triticum aestivum L.)

Abstract: This study was conducted to determine the effects of some priming treatments on seed germination properties, grain yield, and several agromorphological characteristics of bread wheat. Two commonly grown bread wheat varieties, namely Adana-99 and Pandas, were selected for experimentation conducted during the 2007-08 and 2008-09 growing periods. The seeds of the Adana-99 and Pandas wheat varieties were primed with the following: (1) distilled water, (2) 100 ppm indole-3-acetic acid (IAA), ( 3) 2.5% potassium chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…(Andoh and Kobata, 2002). Toklu et al (2015) recorded similar results and declared that distilled water treatments increased seed germination percentage, seedling emergence percentage, and seedling growth rate. The growth parameters increased due to priming methods.…”
Section: Effect Of Seed Priming Techniques On Germination Conductancementioning
confidence: 61%
See 1 more Smart Citation
“…(Andoh and Kobata, 2002). Toklu et al (2015) recorded similar results and declared that distilled water treatments increased seed germination percentage, seedling emergence percentage, and seedling growth rate. The growth parameters increased due to priming methods.…”
Section: Effect Of Seed Priming Techniques On Germination Conductancementioning
confidence: 61%
“…5 hours seed hydro priming has positive effect on growth and yield traits of wheat varieties. Toklu et al (2015) concluded hydropriming treatments as a simple, cheap, and effective methods to improve seed germination and seedling growth in field conditions in Panda and Adana-99.…”
Section: Effect Of Seed Priming Techniques On Germination Conductancementioning
confidence: 99%
“…Four concentrations (5, 10, 15 and 20 g/l) and control (distilled water) of the salts of the priming agents were prepared. Fifty seeds of each of the test seeds were soaked in 200 ml of each of the concentrations for 24hours in sample bottles after which they were removed and rinsed thoroughly in distilled water (Rajpar et al;2006 and Toklu et al;2015), thereafter 15seeds were planted on moistened filter paper in each of the already labeled petri dishes in the Plant physiology laboratory of the Department of Plant Biology, University of Ilorin, Ilorin, Nigeria. Each of the treatments was replicated thrice and arranged in randomized form on the laboratory table.…”
Section: Methodsmentioning
confidence: 99%
“…Seed priming is known as the seed treatment which improves seed performance under environmental condition. It is reported that seed priming is a useful and recommended practice to enhance rapid and uniform emergence for the purpose of achieving high germination rate, high seedling vigor and better yields in vegetables,and floriculture and some field crops (Parera and Cantliffe, 1994;Toklu et al, 2015). Ghassemi-Golezani et al (2008) reported that hydro priming is an eco-friendly simple, and low cost technique, for improving seed germination and seedling vigor of lentils.…”
Section: Introductionmentioning
confidence: 99%